PENGARUH DESTINATION ATTRIBUTE MELALUI MEMORABLE TOURISM EXPERIENCE TERHADAP REVISIT INTENTION (STUDI PADA PENGUNJUNG TAMAN MINI INDONESIA INDAH) - Reyhan Adimas Agung; Naili Farida; Sari Listyorini (Universitas Diponegoro, 2025)
This study aims to determine the relationship between the three variables, namely destination attributes, memorable tourism experience, and revisit intention at TMII. The sample in this study were 100 TMII tourists who visited within the last 6 months. Data were collected through the results of questionnaires given to the sample. The data were analyzed using statistical tools in the form of Smart PLS 4 software and several stages of analysis were carried out, including validity tests, reliability tests, variable influence tests, and significance tests. The results showed that destination attributes have an insignificant effect on revisit intention, destination attributes have a significant effect on memorable tourism experience, memorable tourism experience has a significant effect on revisit intention, and memorable tourism experience has a significant effect in mediating the relationship between destination attributes and revisit intention. The suggestion given to TMII is that the manager can increase tourists' interest in visiting again by optimizing the quality of destination attributes owned and ensuring that this optimization provides a pleasant and memorable visiting experience for tourists. It is hoped that further research can explore the relationship between the three variables with other subjects or with a wider sample.Keyword: Destination Attribute; Memorable Tourism Experience; Revisit Intention Penelitian ini memiliki tujuan untuk mengetahui kaitan antara ketiga variabel, yaitu destination attributes, memorable tourism experience, dan revisit intention pada TMII. Sampel pada penelitian ini adalah 100 orang wisatawan TMII yang berkunjung dalam kurun waktu 6 bulan terakhir. Data dikumpulkan melalui hasil kuesioner yang diberikan pada sampel. Data dianalisis menggunakan alat bantu statistik berupa perangkat lunak Smart PLS 4 dan dilakukan beberapa tahap analisis, diantaranya uji validitas, uji reliabilitas, uji pengaruh variabel, dan uji signifikansi. Hasil penelitian menunjukan bahwa destination attributes berpengaruh tidak signifikan terhadap revisit intention, destination attributes berpengaruh signifikan terhadap memorable tourism experience, memorable tourism experience berpengaruh signifikan terhadap revisit intention, dan memorable tourism experience berpengaruh signifikan dalam memediasi hubungan antara destination attribute dan revisit intention. Saran yang diberikan adalah pengelola dapat meningkatkan minat berkunjung kembali para wisatawan dengan melakukan optimasi terhadap kualitas destination attributes yang dimiliki dan memastikan bahwa optimasi tersebut memberikan pengalaman berkunjung yang menyenangkan dan mengesankan bagi. Diharapkan penelitian selanjutnya dapat menggali hubungan lebih lanjut ketiga variabel dengan subjek lain ataupun dengan sampel yang lebih luas.Kata Kunci: Destination Attribute; Memorable Tourism Experience; Revisit Intention